Study on novel biphenyl chalcone scaffolds: A dual spectroscopic approach for efficient sensing of hydrazine with low concentration - Patel, Paresh Narayan; Tandel, Shivani Nagindas; Deshmukh, Amar Ghanshyam; Patel, Preksha Basant (European Journal of Chemistry, 2023)
Hydrazine and its derivatives, as harmful substances, seriously risk the health of humans and the environment. On the basis of the admirable luminescent properties and low biological harmfulness of the biphenyl moiety, a biphenyl moiety can be combined with a naphthalene ring via the chalcone scaffold easily traced by a nucleophilic group. Therefore, biphenyl chalcones (BPCs) decorated with various naphthalene systems as fluorescent sensors for hydrazine are synthesised by Claisen-Schmidt condensation. The present work describes the comparative studies of two different protocols for the synthesis of three different BPCs. The structures of all novel BPCs were investigated by FT-IR, NMR, and HRMS spectroscopy. These BPCs show a red shift with a fluorescent peak and an enhancement in intensity with increasing solvent polarity from hexane to methanol. Methanol shows strong fluorescence emission; therefore, methanol is used as the solvent in hydrazine sensing experiments. The BPCs display fluorescent variation from yellow to blue fluorescence after binding with hydrazine. These BPCs sensors are able to identify hydrazine in a fast response rate and 5 min response time. The screening study of hydrazine in various soil samples by prepared BPCs is highly efficient. A study of the pH dependence of these probes shows excellent sensitivity in the pH range of 5 to 10.